Pengaruh Dividend Per Share dan Earning Per Share Terhadap Harga Saham Pada Perusahaan Farmasi Yang Terdaftar di Bursa Efek Indonesia Periode 2017-2021 - Fransiska Simanullang; Sairun Simanulang; Imelda Barus (ITB AAS INDONESIA, 2023)
The capital market is a place where securities in the form of stocks and bonds are traded where in this market there are two groups that complement each other, namely investors who have capital to invest in securities and on the other hand there are issuers as issuers of securities that require long-term funds. for the company's needs in increasing its assets which can be obtained by issuing securities (stocks and bonds). The data analysis method used in this study was preceded by testing descriptive statistics, classical assumptions, multiple linear analysis, testing the hypothesis of the coefficient of determination and then at the end by testing the coefficient of determination. The program (software) used for data processing in this study is SPSS version 26.0. The population of this study are pharmaceutical companies listed on the Indonesia Stock Exchange in five years, from 2017 to 2021, totaling 12 companies. The sampling technique used is purposive sampling. The results of the study partially prove that Dividend Per Share (DPS) has no and no significant effect on stock prices in pharmaceutical companies on the Indonesia Stock Exchange in the 2017-2021 period. The results of the study partially prove that Earning Per Share (EPS) has a positive and significant effect on stock prices in pharmaceutical companies on the Indonesia Stock Exchange in the 2017-2021 period. Dividend Per Share (DPS) and Earning Per Share (EPS) simultaneously have a significant effect on stock prices. This means that any changes that occur in the independent variables, namely Dividend Per Share (DPS) and Earning Per Share (EPS) simultaneously or together will affect the Stock Price of Pharmaceutical Companies on the Indonesia Stock Exchange in the 2017-2021 period.